ANALISIS RASIO LIKUIDITAS, PROFITABILITAS, RENTABILITAS EKONOMI DAN LEVERAGE DALAM MEMPREDIKSI FINANCIAL DISTRESS PADA INDUSTRI TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - B31112016, PUTRI AYU YULIANA (Jurnal Manajemen Update, 2016)
Financial distress is a stage of decline in the company's financial condition that occurs prior to the bankruptcy or liquidation characterized by the inability of the company to meet its obligations. This study aims to determine the prediction of financial distress in the textile and garment industry companies listed on the stock exchanges of Indonesia in 2015-2017 based on data for 2009 to 2014 as many as 12 companies that have a complete and audited financial statements. The analytical method used to determine the company's financial distress in this study is to use the method of Altman Z-Score Modification of 1995. By using four variables representing financial ratios Altman Z-Score, the liquidity ratio X1, profitability ratio X2, earning power ratio X3 and the leverage ratio X4, the obtained value of Z-score formula Z = 6,56X1 + 3,26X2 + 6,72X3 + 1,05X4 where the Z value ≤ 1.1 companies that are in financial distress. For the Z value in the range of 1.1 <Z <2.6, then the company is in the gray conditions that allow companies that are in financial condition distress or are in a safe condition. It depends on the discretion of the management company in taking action and making the right decisions and quick in fixing the financial condition of the company. While the value of Z ≥ 2.6, then the company is in a safe condition. These results indicate that the company is predicted to be in financial distress criteria amounted to 83.33 % or 10 companies , and over the years of observation Stock Price Index Industry can’t be an early warning system for investors . Suggested for management and investors to be more carefully , thoughtful and thorough before taking a decision. Keyword : Financial Distress, Financial Ratio, Early Warning System, Altman Z-Score Modification 1995